2020
DOI: 10.1002/pi.6007
|View full text |Cite
|
Sign up to set email alerts
|

High surface area benzimidazole based porous covalent organic framework for removal of methylene blue from aqueous solutions

Abstract: In this study, a highly thermally stable benzimidazole based covalent organic framework (bCOF) was synthesized by the reaction of perlin‐tetracarboxylic anhydride, 5‐aminoisophthalic acid and diaminobenzidine in polyphosphoric acid medium. The synthesized porous bCOF was identified by different techniques. From CO2 adsorption, the micropore surface area of the bCOF was found to be 856 m2 g−1; this synthesized bCOF has a widespread netting construction, and it has various porosity. The TGA results displayed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…When the macromolecular dye is loaded into PI-COF-3, the temperature dependence in the emission spectrum is studied. Then we found that the product had unique luminous properties that Yes Yes [40,45] vary with temperature, indicating that dye-doped PI-COFs can be applied for temperature sensor devices.…”
Section: Adsorption and Separationmentioning
confidence: 92%
See 4 more Smart Citations
“…When the macromolecular dye is loaded into PI-COF-3, the temperature dependence in the emission spectrum is studied. Then we found that the product had unique luminous properties that Yes Yes [40,45] vary with temperature, indicating that dye-doped PI-COFs can be applied for temperature sensor devices.…”
Section: Adsorption and Separationmentioning
confidence: 92%
“…The tube sealing method is carried out under more extreme conditions, and usually requires that the precursor molecules have good solubility in the solvent in order to obtain crystals of good quality The crystals obtained by this method have exceptional crystallinity, but it requires a long reaction period and it is rarely used for large-scale synthesis. In recent years, researchers have been working hard to explore low-cost and large-scale synthesis methods, such as solvothermal synthesis, [17,18,26,27,41,42,44,46,48] condensation polymerization synthesis, [25,45] high-temperature solid-state synthesis, [39] interfacial synthesis, and ionothermal synthesis. [40,45]…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations